A New Home-Based Upper- and Lower-Limb Telerehabilitation Platform with Experimental Validation - Latreche, Ameur; Kelaiaia, Ridha; Chemori, Ahmed; Kerboua, Adlen (Arabian Journal for Science and Engineering, 2023)
The world is witnessing interesting challenges in several fields, including medicine. Solutions to many of these challenges are being developed in the field of artificial intelligence. As a result, artificial intelligence techniques can be used in telerehabilitation to facilitate the work of doctors and to find methods that can be used to better treat methods that can be used to better treat patients. Motion rehabilitation is an essential procedure for elderly people and patients undergoing physiotherapy after physical procedures such as surgery for the anterior cruciate ligament (ACL), a frozen shoulder. To regain normal motion, the patient must participate in rehabilitation sessions. Furthermore, telerehabilitation has become a significant trend in research studies because of the COVID-19 pandemic, which is continuing to affect the world through the delta and the omicron variants, and other epidemics. In addition, because of other special issues like the vastness of the desert area in Algeria and the lack of facilities, it is ideal to avoid requiring patients to travel for all of their rehabilitation sessions; patients should be able to perform their rehabilitation exercises at home. Thus, telerehabilitation could lead to promising developments in this field. Therefore, our project’s goal is to develop a website for telerehabilitation that can be used to facilitate rehabilitation from a distance. We also want to track the progress of patients’ range of motion (ROM) in real time using artificial intelligence techniques, by controlling the angles of the motion of a limbs about a joint.